2021
DOI: 10.1186/s40729-021-00366-3
|View full text |Cite
|
Sign up to set email alerts
|

Does the pre-operative buccal soft tissue level at teeth or gingival phenotype dictate the aesthetic outcome after flapless immediate implant placement and provisionalization? Analysis of a prospective clinical case series

Abstract: Background Immediate implant placement (IIP) often is related to mid-buccal recession in literature. To draw conclusions about the behavior of the soft tissues following IIP, pre-operative aesthetic measurements have to be taken into account. The aim of analysis of these prospective clinical case series data was to elucidate whether the pre-operative buccal soft tissue level (STL) or gingival phenotype influence the 1-year pink aesthetic outcome after performing flapless immediate implant place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(34 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…Seven studies allowed for small facial dehiscence or fenestration defects of up to 3 mm (Bonnet et al, 2018; Bruno et al, 2014; Bushahri et al, 2021; Hartlev et al, 2013; Ma et al, 2019; McAllister et al, 2012; Migliorati et al, 2015). Larger defects or complete lack of facial bone was reported in 11 studies (Calvo‐Guirado et al, 2009; Cooper et al, 2014; Groenendijk et al, 2021; Kolerman, Nissan, Rahmanov, et al, 2016; Noelken et al, 2011; Noelken, Moergel, Pausch, et al, 2018; Norton, 2011; Rosa et al, 2014; Slagter et al, 2021; Valentini et al, 2010; Zuiderveld et al, 2018). The thickness of facial bone was only considered in eight studies (Bittner et al, 2020; Bushahri et al, 2021; Cardaropoli et al, 2019; Groenendijk et al, 2017; Kolerman, Nissan, Rahmanov, et al, 2016; Noelken, Moergel, Pausch, et al, 2018; Seyssens et al, 2020; Yang et al, 2019), with thicknesses ranging from 0 to 1.6 mm, and no studies reported a minimum of 1 mm facial bone thickness as an inclusion criterion.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…Seven studies allowed for small facial dehiscence or fenestration defects of up to 3 mm (Bonnet et al, 2018; Bruno et al, 2014; Bushahri et al, 2021; Hartlev et al, 2013; Ma et al, 2019; McAllister et al, 2012; Migliorati et al, 2015). Larger defects or complete lack of facial bone was reported in 11 studies (Calvo‐Guirado et al, 2009; Cooper et al, 2014; Groenendijk et al, 2021; Kolerman, Nissan, Rahmanov, et al, 2016; Noelken et al, 2011; Noelken, Moergel, Pausch, et al, 2018; Norton, 2011; Rosa et al, 2014; Slagter et al, 2021; Valentini et al, 2010; Zuiderveld et al, 2018). The thickness of facial bone was only considered in eight studies (Bittner et al, 2020; Bushahri et al, 2021; Cardaropoli et al, 2019; Groenendijk et al, 2017; Kolerman, Nissan, Rahmanov, et al, 2016; Noelken, Moergel, Pausch, et al, 2018; Seyssens et al, 2020; Yang et al, 2019), with thicknesses ranging from 0 to 1.6 mm, and no studies reported a minimum of 1 mm facial bone thickness as an inclusion criterion.…”
Section: Resultsmentioning
confidence: 95%
“…Flapless immediate implant placement was performed in 49 of the included studies (Arora & Ivanovski, 2018a, 2018b; Berberi, Sabbagh, et al, 2014; Bittner et al, 2020; Block et al, 2009; Bonnet et al, 2018; Bruno et al, 2014; Bushahri et al, 2021; Cabello et al, 2013; Canullo et al, 2010; Canullo, Goglia, et al, 2009; Canullo & Rasperini, 2007; Cardaropoli et al, 2015, 2019; Cosyn et al, 2016; Crespi et al, 2008; Degidi et al, 2013; Ferrara et al, 2006; Grandi et al, 2013; Grandi, Garuti, Samarani, et al, 2012; Groenendijk et al, 2017, 2021; Groisman et al, 2003; Hartlev et al, 2013; Kan et al, 2011; Khzam et al, 2014; Ma et al, 2019; Malchiodi et al, 2013; Menchini‐Fabris et al, 2019; Migliorati et al, 2015; Mijiritsky et al, 2021; Noelken et al, 2011; Noelken, Moergel, Pausch, et al, 2018; Paul & Held, 2013; Pieri et al, 2011; Ribeiro et al, 2008; Rosa et al, 2014; Saedi Germi et al, 2020; Sato et al, 2017; Seyssens et al, 2020; Shanelec, 2005; Slagter et al, 2021; Spinato et al, 2012; Tarnow et al, 2014; Tortamano et al, 2010; Van Nimwegen et al, 2016; Vidigal Jr. et al, 2017; Yang et al, 2019; Zuiderveld et al, 2018). The use of a minimal mucoperiosteal flap was reported in three studies (Berberi, Noujeim, et al, 2014; Cosyn et al, 2011; Cristalli et al, 2015), with a further 11 studies reporting raising a full‐thickness mucoperiosteal flap for the purpose of extraction and immediate implant placement ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 25 The amount of gingival recession at the extraction site. A gingival recession of more than 3 mm is considered to be associated with risk of soft tissue deficiency following IIP 6,29 (Figure 4B). Determination of soft tissue phenotype: this parameter can be either thin or thick and plays a key role in determination of future peri‐implant soft tissue 25,27 …”
Section: Proposal Of a New Classification Systemmentioning
confidence: 99%